2004
DOI: 10.1158/0008-5472.can-04-1168
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Structure for Epidermal Growth Factor Receptor Bound to GW572016 (Lapatinib)

Abstract: GW572016 (Lapatinib) is a tyrosine kinase inhibitor in clinical development for cancer that is a potent dual inhibitor of epidermal growth factor receptor (EGFR, ErbB-1) and ErbB-2. We determined the crystal structure of EGFR bound to GW572016. The compound is bound to an inactive-like conformation of EGFR that is very different from the activelike structure bound by the selective EGFR inhibitor OSI-774 (Tarceva) described previously. Surprisingly, we found that GW572016 has a very slow off-rate from the purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
412
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,003 publications
(431 citation statements)
references
References 28 publications
18
412
0
1
Order By: Relevance
“…Other analogs in series B are also less active than their isomeric counterparts in series A, with the exception of the simple acetylene derivative 10, which had similar potency to 6 in the ErbB-2 cellular assay. The x-ray crystal structure of erlotinib and lapatinib bound to EGFR have both been reported (11,12). As described previously, the structure of lapatinib in EGFR revealed that the bulky benzyloxy aniline head group induced a significant conformational shift of the enzyme relative to erlotinib.…”
Section: Enzyme and Cellularmentioning
confidence: 67%
See 1 more Smart Citation
“…Other analogs in series B are also less active than their isomeric counterparts in series A, with the exception of the simple acetylene derivative 10, which had similar potency to 6 in the ErbB-2 cellular assay. The x-ray crystal structure of erlotinib and lapatinib bound to EGFR have both been reported (11,12). As described previously, the structure of lapatinib in EGFR revealed that the bulky benzyloxy aniline head group induced a significant conformational shift of the enzyme relative to erlotinib.…”
Section: Enzyme and Cellularmentioning
confidence: 67%
“…The inhibitor aniline substituent binds in the ''backpocket'' of the enzyme in a manner similar to that of lapatinib in EGFR ( Fig. 3B) (12). Of key significance, the thienopyrimidine inhibitor ErbB-4 structure revealed a covalent bond between the Cys-803 sulfhydryl group and the acetylene terminus of the inhibitor ( Fig.…”
Section: Enzyme and Cellularmentioning
confidence: 93%
“…The recent discovery that mutations in the epidermal growth factor receptor (EGFR) confer sensitivity to EGFR inhibitors in non-small-cell lung cancer patients raises the possibility that acquired resistance to these drugs may occur through an analogous mechanism (20,23). The two most widely studied EGFR inhibitors, gefitinib and erlotinib, are thought to bind EGFR in the active conformation, whereas lapatinib, a third compound in clinical trials, binds EGFR in an inactive-like conformation (24,25). Comparative studies of these compounds may reveal distinct resistance mechanisms and could provide rationale for combination therapy, or for a search for additional, more conformation-tolerant EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…19 Unlike erlotinib and gefitinib, lapatinib (Tykerb/Tyverb) is a dual tyrosine kinase inhibitor that forms relatively selective and unique complexes with both EGFR and HER2. 20 Several clinical trials established lapatinib's activity, together with chemotherapy, in the treatment of patients with HER2-positive advanced breast cancer previously treated with trastuzumab and chemotherapy. 21 Afatinib is the first clinically approved TKI of the second generation of HER/ERBB inhibitors, designed to have more potent inhibition of EGFR and to overcome the EGFR T790M resistance mutation.…”
Section: Targeted Cancer Therapy Directed At the Egfr (Her/ Erbb) Familymentioning
confidence: 99%